2021
DOI: 10.3389/fgene.2021.699242
|View full text |Cite
|
Sign up to set email alerts
|

DNASE1L3 as a Novel Diagnostic and Prognostic Biomarker for Lung Adenocarcinoma Based on Data Mining

Abstract: Previous researches have highlighted that low-expressing deoxyribonuclease1-like 3 (DNASE1L3) may play a role as a potential prognostic biomarker in several cancers. However, the diagnosis and prognosis roles of DNASE1L3 gene in lung adenocarcinoma (LUAD) remain largely unknown. This research aimed to explore the diagnosis value, prognostic value, and potential oncogenic roles of DNASE1L3 in LUAD. We performed bioinformatics analysis on LUAD datasets downloaded from TCGA (The Cancer Genome Atlas) and GEO (Gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Moreover, CDK1 and MAD2L1 were reported by Lu et al as prognostic markers in rhabdomyosarcoma [ 38 ]. To the best of our knowledge, this is the first comprehensive study to assess the expression of MAD2L1 in HCC using TCGA database [ 39 ]. We provided compelling evidence that MAD2L1 gene expression levels are significantly higher in HCC patients than in adjacent paraneoplastic tissues, as confirmed by IHC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CDK1 and MAD2L1 were reported by Lu et al as prognostic markers in rhabdomyosarcoma [ 38 ]. To the best of our knowledge, this is the first comprehensive study to assess the expression of MAD2L1 in HCC using TCGA database [ 39 ]. We provided compelling evidence that MAD2L1 gene expression levels are significantly higher in HCC patients than in adjacent paraneoplastic tissues, as confirmed by IHC.…”
Section: Discussionmentioning
confidence: 99%
“…DNASE1L3 is correlated with breast cancer signalling, renal clear cell carcinoma staging 10,11 . Furthermore, DNASE1L3 was found to be a potential prognostic biomarker in lung adenocarcinoma and colon cancer 12,13 . Recent studies reported that DNASE1L3 could inhibit glycolysis in hepatoma cells and promote the tricarboxylic acid cycle involved in PTPN2‐HK2 and CEBPβ‐p53‐PFK1 pathways, thereby inhibiting HCC progression 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Furthermore, DNASE1L3 was found to be a potential prognostic biomarker in lung adenocarcinoma and colon cancer. 12,13 Recent studies reported that DNASE1L3 could inhibit glycolysis in hepatoma cells and promote the tricarboxylic acid cycle involved in PTPN2-HK2 and CEBPβ-p53-PFK1 pathways, thereby inhibiting HCC progression. 14,15 Based on various bioinformatic analyses, we found that the role of DNASE1L3 is associated with HCC proliferation, invasion and metastasis, but the underlying molecular mechanisms is unclear.…”
mentioning
confidence: 99%
“…A previous study reported that DNASE1L3 is downregulated in LUAD (12). An additional study found that mRNA and protein expression levels of DNASE1L3 in patients with LUAD are significantly lower than those in normal tissue and low expression of DNASE1L3 is significantly correlated with higher pathological stage, T stage and poor prognosis, making it an independent factor for predicting the overall survival rate (13). The specific role of DNASE1L3 in LUAD, to the best of our knowledge, has not yet been reported.…”
Section: Introductionmentioning
confidence: 85%